Potensi Larvasida Ekstrak Daun Alpukat (Persea americana) terhadap Larva Nyamuk Aedes aegypti - Wenas, Desy Muliana; Fajrin, Muhammad Nur; Subaryanti, Subaryanti (Sainstech Farma: Jurnal Ilmu Kefarmasian, 2023)
Avocado (Persea americana Mill.) leaves contain saponins, tannins, flavonoids and alkaloids that have potential as larvicides. The purpose of this study was to determine the larvicidal activity of ethanol extract of avocado (Persea americana) leaves against Aedes aegypti larvae. The test was carried out on 210 larvae which were divided intro 7 groups, namely group I, II, III, IV, V which were ethanol extract of avocado leaves with concentration of 0,1%; 0,5%; 1%; 1,5%; and 2%. Positive control (group VI) was given Temephos 0,01% solution and group VII as negative control was only given Aquadest. Each treatment groups were observed for larvae death and counted every hour for 24 hours. LC50 and LT50 values were calculated using probit analysis. The results showed that ethanol extract of avocado leaf had larvicidal activity against Aedes aegypti larvae with LC50 = 0,03% at 3 hours and LT50 = at 1 hour 42 minutes. The ethanol extract of avocado leaf had a potential as larvicidal against Aedes aegypti larvae.